Menganalisis Ekonomi Dalam Islam Yang Berkaitan Dengan Aspek Hukum Dalam Bisnis - Mardiansyah, Arbi; Syafril, Rizki (CV. ITTC INDONESIA, 2024)
Islamic economics is a scientific discipline that integrates economic principles with Islamic teachings. In the Islamic economic framework, business activities are not only viewed from a profit perspective, but also from an ethical and social responsibility perspective. The Islamic economic approach to business rejects the practices of riba (interest), gharar (uncertainty), and maysir (speculation), and requires the implementation of a system based on profit sharing such as mudharabah and musyarakah. In addition, in carrying out business, it must always be ensured that the goods and services traded are halal and good, in accordance with the principles of halal and thayyib. The principles of economic growth in Islam include tawhid, rubiyyah, caliphate, and tazkiyah. It is hoped that by complying with sharia business ethics, a Muslim entrepreneur can maintain his business because he will always receive the blessings of Allah SWT both in this world and in the hereafter.